2008
DOI: 10.1021/ma071429e
|View full text |Cite
|
Sign up to set email alerts
|

SANS Investigation and Conductivity of Pure and Salt-Containing Poly(bismethoxyphosphazene)

Abstract: Poly(bismethoxyphosphazene) (PBMP) was synthesized, giving polymer melts with T g ) -70.9 °C. The chain dynamics of melts and DMF solutions of poly(bismethoxyphosphazene) (PBMP) was investigated by Small-Angle Neutron Scattering (SANS). The radius of gyration R g was found as 144.7 ( 0.2 Å, and the average MW from SANS was 95000 Da. DMF revealed to be a good solvent for this polymer. From the scattering intensity of polymer solutions for high q-data, the slope was -1.647 in almost exact agreement with the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…As expected for glass-forming polymer melts, all data are consistently described by the Vogel−Fulcher−Tammann (VFT) equation τ = τ 0 exp true[ B T T 0 true] where B = 1150 K and T 0 = 170 K. In previous studies, a VFT temperature dependence was also observed for the α-process of polyphosphazenes featuring bulkier side groups, e.g., for poly[bis(trifluorethoxy)phosphazene] (PFEP). Extrapolating the present VFT fit to lower temperatures, a correlation time of τ ≈ 100 s is reached in the vicinity of the calorimetric glass transition, T g = 191 K, confirming that the STE experiments probe the α-process. In agreement with this conclusion, reinspection of Figure shows that the observed dynamical process leads to a complete decay of F 2 , as expected for isotropic reorientation associated with the α-process, while restricted reorientation typical of a β-process would leave a finite residual correlation at t m ≫ τ.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…As expected for glass-forming polymer melts, all data are consistently described by the Vogel−Fulcher−Tammann (VFT) equation τ = τ 0 exp true[ B T T 0 true] where B = 1150 K and T 0 = 170 K. In previous studies, a VFT temperature dependence was also observed for the α-process of polyphosphazenes featuring bulkier side groups, e.g., for poly[bis(trifluorethoxy)phosphazene] (PFEP). Extrapolating the present VFT fit to lower temperatures, a correlation time of τ ≈ 100 s is reached in the vicinity of the calorimetric glass transition, T g = 191 K, confirming that the STE experiments probe the α-process. In agreement with this conclusion, reinspection of Figure shows that the observed dynamical process leads to a complete decay of F 2 , as expected for isotropic reorientation associated with the α-process, while restricted reorientation typical of a β-process would leave a finite residual correlation at t m ≫ τ.…”
Section: Resultssupporting
confidence: 76%
“…Synthesis and characterization of the studied PBMP- d 6 were described in ref . A molecular weight of M w = 1.04 × 10 5 g/mol and a glass transition temperature of T g = 191 K were reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mobility of the polymer segments is enhanced. SANS measurements support this: the BMP molecules in the liquid polymer behave like statistical coil molecules [41]. Therefore, it is not surprising that the conductivities of salt solutions in BMP are as high as those of MEEP with dissolved lithium triflate.…”
Section: Methodsmentioning
confidence: 78%
“…83 The conductivity of salt-containing poly(bismethoxyphosphazene) has been evaluated. 84 The functionalization of polyamide-and polyvinylalcohol-surfaces with polydichlorophosphazene which was later functionalized by 2,2,2-trifluoroethanol has been reported. 85,86 The hydrophobic properties of these surfaces was probed through surface contact angle measurements.…”
Section: Polyphosphazenes Polyheterophosphazenes and Related Polymersmentioning
confidence: 99%